Retrospective surveillance of metabolic parameters affecting reproductive performance of Japanese Black breeding cows - Watanabe, Urara (The Korean Society of Veterinary Science, 2014)
This retrospective study was conducted to confirm the relationship between pre- and postpartum metabolic parameters and postpartum reproductive performance and to clarify seasonal characteristics of the metabolic parameters by using our metabolic profile test (MPT) database of Japanese Black breeding herds. In evaluation 1, MPT databases of blood samples from multiparous cows collected prepartum and postpartum were divided into two groups according to calving interval, and each MPT parameter was compared. In evaluation 2, the same MPT databases used in evaluation 1 were divided into two groups according to the sampling period. Significant differences were found in the prepartal total protein and postpartal γ-glutamyltransferase in evaluation 1. In evaluation 2, significant differences were found in the prepartal and postpartal total protein, albumin/globulin ratio, and glucose. Clear seasonal differences in MPT results emphasized the usefulness of the MPT in breeding cattle herds fed home-pasture roughage and suggest that unsatisfactory reproductive performance during hot periods reflects inadequate nutritional content of the diet and possible reduced feed intake due to heat stress.